Evaluating urban ecosystem resilience using the DPSIR framework and the ENA model: A case study of 35 cities in China. (September 2021) - Zhao, Ruidong; Fang, Chuanglin; Liu, Haimeng; Liu, Xiaoxiao
Highlights: A novel integrated evaluation framework is proposed to assess urban ecosystem resilience. Holistic analysis of action paths and causality between DPSIR components. Material flow and energy flows are quantified to analyze the sustainability of an urban ecological network. The resilience of ecosystem networks can be strengthened by increasing redundancy thus ensuring ecological security. Abstract: Rapid urbanization and large-scale industrialization in China have produced problems that affect resources, the environment, and local ecology, which are obstacles to urban ecosystem resilience. Ecosystem resilience is critical for recovery from adverse natural events and the security of urban ecosystems. In this paper, we constructed the evaluation indexes of urban ecological resilience systems (UERs) using DPSIR framework to quantify urban ecological resilience index (UERI) for 35 major cities in China, and we evaluated the sustainability of UER networks using ecological network analysis. The results show that: (1) UERI generally increases annually, but it gradually decreases geographically from developed coastal areas to developing inland areas; (2) factors that affect the DPSIR components Drivers, State and Responses significantly increase UERI, and factors that affect Pressures and Impact decrease UERI; all paths of DPSIR passed the causal hypotheses test; (3) the ideal value for resilience of an urban ecosystem network was 0.550; we found that resilience in 2005 was 0.659, and in 2010 was 0.512 but in 2015 was 0.462 (<0.550). As ecosystem vulnerability and adverse ecological risks continue to increase, it is critical for cities to transform themselves to increase ecological security and become more resilient.